The environmental benefits from road pricing - Santos, G; Rojey, L; Newbery, D (Department of Applied Economics, University of Cambridge, 2000)
In this paper the environmental benefits of optimal tolls in eight English towns are estimated. Tolls are simulated using the SATURN model (Simulation and Assignment of Traffic to Urban Road Networks) with associated software to simulate the changes in traffic patterns resulting from cordon tolls. With these results the optimal tolls are computed together with the resulting levels and speeds of traffic in each of our study towns. Changes in vehicle emissions are estimated and reduction in health and global warming costs computed. One of the main results is that any toll designed to reduce traffic congestion would yield positive environmental benefits.